Development of Spin Game Learning Media in Islamic Religious Education Subjects in Elementary Schools - Auliya, Alfa Maulidiina; Takwim, Mardi; Mawardi, Mawardi; Kusdarianto, Indra (Educational Journal of Learning Technology, 2024)
This study aims to determine the development of "spin game" learning media in Islamic Religious Education subjects at SD Negeri 196 Ammassangan, West Malangke District, North Luwu Regency, and to determine the feasibility of the learning media. The research method used is research and development (R&D) with the ADDIE approach, involving 20 students in grade V as research subjects. The object of this research is the "spin game" learning media in Islamic Religious Education. Data collection techniques include interviews, observations, media validation sheets, and documentation. The study results show that the development of "spin game" learning media has gone through the validation stage by media, material, and language experts and is considered suitable for use in the learning process. This study emphasizes the importance of developing "spin game" learning media to improve students' understanding of Islamic Religious Education in schools.